2010
DOI: 10.1016/j.virol.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

The neurovirulence and neuroinvasiveness of chimeric tick-borne encephalitis/dengue virus can be attenuated by introducing defined mutations into the envelope and NS5 protein genes and the 3′ non-coding region of the genome

Abstract: Tick-borne encephalitis (TBE) is a severe disease affecting thousands of people throughout Eurasia. Despite the use of formalin-inactivated vaccines in endemic areas, an increasing incidence of TBE emphasizes the need for an alternative vaccine that will induce a more durable immunity against TBE virus (TBEV). The chimeric attenuated virus vaccine candidate containing the structural protein genes of TBEV on a dengue virus genetic background (TBEV/DEN4) retains a high level of neurovirulence in both mice and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 38 publications
1
55
0
1
Order By: Relevance
“…S1 in the supplemental material. RNA transcripts derived from these modified TBEV/DEN4 cDNA clones were generated by transcription with SP6 polymerase and used to transfect Vero or C6/36 cells in the presence of Lipofectamine as described previously (9,33). Eight viruses [designated 2x mir-124aT(1,2), mir-9T-124aT(1,2), mir-9T-124aT-124aT(1,2,3), 3x mir-124aT(1,2,3), 3x mir-124aT(1,2,4), 3x mir124aT(1,2,5), 4x mir-124aT (1,2,3,4), and 4x mir-124aT(1,2,3,5)] carrying 2, 3, or 4 copies of targets (T stands for target) for mir-124a and/or mir-9 at the insertion sites (the site numbers are shown in the parentheses) were recovered from Vero cells, biologically cloned by two or three terminal dilutions, and amplified by two passages in Vero cells.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 in the supplemental material. RNA transcripts derived from these modified TBEV/DEN4 cDNA clones were generated by transcription with SP6 polymerase and used to transfect Vero or C6/36 cells in the presence of Lipofectamine as described previously (9,33). Eight viruses [designated 2x mir-124aT(1,2), mir-9T-124aT(1,2), mir-9T-124aT-124aT(1,2,3), 3x mir-124aT(1,2,3), 3x mir-124aT(1,2,4), 3x mir124aT(1,2,5), 4x mir-124aT (1,2,3,4), and 4x mir-124aT(1,2,3,5)] carrying 2, 3, or 4 copies of targets (T stands for target) for mir-124a and/or mir-9 at the insertion sites (the site numbers are shown in the parentheses) were recovered from Vero cells, biologically cloned by two or three terminal dilutions, and amplified by two passages in Vero cells.…”
Section: Methodsmentioning
confidence: 99%
“…Eight viruses [designated 2x mir-124aT(1,2), mir-9T-124aT(1,2), mir-9T-124aT-124aT(1,2,3), 3x mir-124aT(1,2,3), 3x mir-124aT(1,2,4), 3x mir124aT(1,2,5), 4x mir-124aT (1,2,3,4), and 4x mir-124aT(1,2,3,5)] carrying 2, 3, or 4 copies of targets (T stands for target) for mir-124a and/or mir-9 at the insertion sites (the site numbers are shown in the parentheses) were recovered from Vero cells, biologically cloned by two or three terminal dilutions, and amplified by two passages in Vero cells. Virus titer was determined in Vero cells using a plaque-forming assay (PFA) as described previously (9,33). To verify the presence of the introduced miRNA target insertions in the virus genome, RNA for each virus was isolated, and the consensus sequence of the genome was determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of viral determinants modulating the intrinsic virulence of the virus within its host have been identified and have been shown to affect either the binding properties (7,11,33,37) or the replication efficiency (20,34) of DENV. Such knowledge has proven useful for the development of live attenuated DENV vaccine candidates (10,17,46). A number of animal models have been reported that partially reproduce some of the clinical features of human DEN disease, such as hemorrhage or increased vascular permeability (16).…”
mentioning
confidence: 99%
“…Thus, the regions other than the prM and E proteins are also responsible for the neuroinvasiveness of TBEV. Several reports indicated amino acid changes in the NS proteins affect the neuroinvasiveness of tick-borne flaviviruses (24,25) and mosquito-borne flaviviruses (26)(27)(28)(29)(30). Multiplication of TBEV/OHF-ME in the brain was similar to that of parental TBEV.…”
Section: Discussionmentioning
confidence: 99%